Evapotranspiration Rates and Water Utilization of Moth bean under two Soil Moisture Conditions - Singh, R S; Rao, A S; Joshi, N L; Ramakrishna, Y S (Annals of Arid Zone, 2016)
Moth bean (Vigna aconitifolia (Jacq.) Marechal) was grown under rainfed and I()()% potential evapotranspiration (PET) irrigation (unstressed) conditions to quantify the influence of moisture availability on evapotranspiration (ET) rate, and water and heat use efficiencies. The experiment was carried out in gravimetric lysimeters, installed at Central Arid Zone Research Institute, Jodhpur, during 199] and 1992. The evapotranspiration (ET) rate from 100% PET (unstressed) crop was maximum (6.6 mm daiJ ) during 7th week after sowing, and lowest (2.2 mm dai1) during crop emergence stage. The maximum evapotranspiration rate coincided with peak pod formation stage in the crop. Water use efficiency of the crop was 2.3 to 3.5 and 2.2 to 2.4 kg ha’l mm’l for unstressed and rainfed crop, respectively. At cardinal temperatures of 8Â°C (base temperature below which moth bean development ceases), 33Â°C (optimal temperature for development) and 45Â°C (maximum temperature at and above which no development takes place), the crop required 135] to ]569Â°Cd growing degree days (thermal time) to reach physiological maturity. Linear relationship was developed between thermal time and leaf tip appearance. The leaf tip appearance on the main shoot of moth bean in relation Â·to the thermal time was linear under both moisture conditions, requiring about 52 to 58Â°Cd leaf’. However, leaf tip appearance on primary branch was slightly faster and required 49 to 53Â°Cd for each new leaf. Appearance of first primary branch was earlier (at about 300Â° Cd after emergence) under the unstressed condition as compared to the rainfed crop under the potential ET (at 360Â°Cd). Hence, it may be concluded that despite low water requirements, the crop growth is considerahly influenced by. the moisture availability during crop growing period in the region.